Modern management of rheumatoid arthritis - with a focus on biologic therapies - Isaacs, John (Henry Stewart Talks, 2020)
Pathology of rheumatoid arthritis, Management of rheumatoid arthritis, Biological therapies for rheumatoid arthritis, TNF inhibitors, non-TNF inhibitors, and biosimilars, Clinical trials for rheumatoid arthritis